Global epigenetic alterations of mesenchymal stem cells in obesity: the role of vitamin C reprogramming. Issue 7 (3rd July 2021) - Afarideh, Mohsen; Thaler, Roman; Khani, Farzaneh; Tang, Hui; Jordan, Kyra L.; Conley, Sabena M.; Saadiq, Ishran M.; Obeidat, Yasin; Pawar, Aditya S.; Eirin, Alfonso; Zhu, Xiang-Yang; Lerman, Amir; et al.
ABSTRACT: Obesity promotes dysfunction and impairs the reparative capacity of mesenchymal stem/stromal cells (MSCs), and alters their transcription, protein content, and paracrine function. Whether these adverse effects are mediated by chromatin-modifying epigenetic changes remains unclear. We tested the hypothesis that obesity imposes global DNA hydroxymethylation and histone tri-methylation alterations in obese swine abdominal adipose tissue-derived MSCs compared to lean pig MSCs. MSCs from female lean (n = 7) and high-fat-diet fed obese (n = 7) domestic pigs were assessed using global epigenetic assays, before and after in-vitro co-incubation with the epigenetic modulator vitamin-C (VIT-C) (50 μg/ml). Dot blotting was used to measure across the whole genome 5-hydroxyemthycytosine (5hmC) residues, and Western blotting to quantify in genomic histone-3 protein tri-methylated lysine-4 (H3K4me3), lysine-9 (H3K9me3), and lysine-27 (H3K27me3) residues. MSC migration and proliferation were studied in-vitro. Obese MSCs displayed reduced global 5hmC and H3K4m3 levels, but comparable H3K9me3 and H3K27me3, compared to lean MSCs. Global 5hmC, H3K4me3, and HK9me3 marks correlated with MSC migration and reduced proliferation, as well as clinical and metabolic characteristics of obesity. Co-incubation of obese MSCs with VIT-C enhanced 5hmC marks, and reduced their global levels of H3K9me3 and H3K27me3. Contrarily, VIT-C did not affect 5hmC, and decreased H3K4me3 in lean MSCs. Obesity induces global genomic epigenetic alterations in swine MSCs, involving primarily genomic transcriptional repression, which are associated with MSC function and clinical features of obesity. Some of these alterations might be reversible using the epigenetic modulator VIT-C, suggesting epigenetic modifications as therapeutic targets in obesity.